A Rigorous Quasi‐Experimental Design to Evaluate the Causal Effect of a Mandatory Divorce Education Program. (January 2015) - deLusé, Stephanie R.; Braver, Sanford L.
<x xml:space="preserve">Abstract</x> All couples with minor children who filed for divorce within a specific 6‐week period (N = 191 couples) in one jurisdiction were ordered to attend a divorce education program. The control group included about 20 couples randomly selected from each of six 6‐week intervals before and six 6‐week intervals after the treatment interval (N = 243 couples). Archival records were searched for variables such as legal and residential custody award, visitation percentage, and relitigation. The impact of the program was assessed by evaluating, for each variable, whether the data for program interval departed from the straight (regression) line drawn through all the control group intervals. Only the visitation time award significantly differed: 27.75% for treatment couples and 22.46% for control couples. Analyses show that the father's attendance at the program primarily accounts for the difference. Key Points for the Family Court Community There are considerable methodological weaknesses in most of the existing evaluations of divorcing parent education programs. Stronger, more scientifically rigorous—and thus persuasive—designs are possible in court settings, such as the regression discontinuity quasi‐experimental design we feature here. Archival records, such as various court filings, are a rich and relatively untapped source of data. Being mandated to attend a single 2‐hour divorcing parent education class caused an increase in the visitation time award in divorce decrees. There is a disconnect between being mandated by a judge to attend a program and actual attendance.